Clinical Study of Flumazenil Antagonizing Remimazolam on Nausea and Vomiting After Gynecologic Day Surgery [Letter] - Satici MH; Altay N (Dove Medical Press, 2024)
Muhammed Halit Satici,1 Nuray Altay2 1University of Health Sciences, Konya City Hospital Department of Anesthesiology and Reanimation, Konya, Turkey; 2Harran University, Faculty of Medicine, Department of Anesthesiology and Reanimation, Şanlıurfa, TurkeyCorrespondence: Muhammed Halit Satici, University of Health Sciences, Konya City Hospital, Department of Anesthesiology and Reanimation, Akabemahallesi, Adana çevreyolu, Cad. No: 135/1, Karatay, Konya, 42020, Turkey, Tel +905455636333, Email halit_satici@hotmail.com